2014
DOI: 10.1097/hcm.0000000000000026
|View full text |Cite
|
Sign up to set email alerts
|

The Negative Impact of Organizational Cynicism on Physicians and Nurses

Abstract: Despite the potentially severe consequences that could result, there is a paucity of research on organizational cynicism within US healthcare providers. In response, this study investigated the effect of cynicism on organizational commitment, job satisfaction, and interest in leaving the hospital for another job in a sample of 205 physicians and 842 nurses. Three types of cynicism were investigated: trait (dispositional), global (directed toward the hospital), and local (directed toward a specific unit or depa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 25 publications
3
20
0
2
Order By: Relevance
“…This argument is supported by Volpe et al. () who find that change cynicism explains about half of the variance in job satisfaction among the nurses and physicians they surveyed. Watt and Piotrowski () also provide evidence that CAOC has a significant negative association with work engagement.…”
Section: Consequences Of Organisational Changementioning
confidence: 64%
See 1 more Smart Citation
“…This argument is supported by Volpe et al. () who find that change cynicism explains about half of the variance in job satisfaction among the nurses and physicians they surveyed. Watt and Piotrowski () also provide evidence that CAOC has a significant negative association with work engagement.…”
Section: Consequences Of Organisational Changementioning
confidence: 64%
“…Abraham's (2000) study provides evidence to support the idea that CAOC is associated with job dissatisfaction because employees do not perceive any potential improvement to their job arising from the proposed changes. This argument is supported by Volpe et al (2014) who find that change cynicism explains about half of the variance in job satisfaction among the nurses and physicians they surveyed. Watt and Piotrowski (2008) also provide evidence that CAOC has a significant negative association with work engagement.…”
Section: Consequences Of Organisational Changementioning
confidence: 81%
“…This result is in agreement with the findings of Kudo et al [24] who declared that cynicism has long been a major concern for the modern organization which induces negative emotions that causes bad emotional status for employees. In the same line, a study conducted in USA, by Volpe et al [25] showed that organizational cynicism was prominent among USA health care workers. Also, a study conducted by Aly et al [12] at Alexanderia University, Egypt, reported that attitudes of organizational cynicism among nurses was high.…”
Section: Discussionmentioning
confidence: 90%
“…The results of the current study are in the same line with the Egyptian study in 2013 and others from 1997 to 2014 in other countries that presented the detrimental effect of organizational cynicism on employees' attitude. [2,6,25,[30][31][32][33][34] It's evident that the undesirable outcomes of organizational cynicism are nearly the same at diverse settings in the world. [12] Finally, organizational cynicism is a destructive perspective an employee holds toward his/her organization.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Lee, Jeaong, and Seo (2016) for patient care and adopt authentic and transformational leadership approaches (Mantler et al, 2015), and all managers should receive emotional intelligence training in order to be successful in an environment that includes continuous transformation and uncertainties (Nafei, 2013). Being transparent in management, reducing managers' own cynicism, introducing and explaining changes (Volpe et al, 2014), announcing all successful practices, no matter how small (Nafei, 2013), emotional support and empathic listening of employees (Shanley, 2007), creating organisational policies and procedures based on their needs and hiring optimistic people to positively affect other employees as well (Koçoğlu, 2014) and benefiting from senior and/or respected members of the organisation at the time of change are emphasized. All these approaches can positively affect job satisfaction and organisational commitment of nurses and nurse managers.…”
Section: Discussionmentioning
confidence: 99%